Assessing the drivers of sexual behavior among youth and its social determinants in Nepal - Grishu Shrestha; Reecha Piya; Sampurna Kakchapati; Parash Mani Sapkota; Deepak Joshi; Sushil Chandra Baral (PLoS ONE, 2025)
Introduction Sexual behavior among youth is a public health concern, particularly in contexts where cultural norms, socio-economic factors, and access to comprehensive sexual education play pivotal roles. This paper aims to examine the determinants of sexual behavior among Nepali youths. Methods This study analyzed data from 7,122 individuals aged 15–24 years from the Nepal Demographic and Health Survey (NDHS) 2022, focusing on a nationally representative sample. This study assessed the prevalence of sexual behaviors, including premarital sex, recent sexual activity, and multiple sexual partners. Determinants examined included socio-demographic characteristics, media use, smoking, and alcohol consumption. Bivariate and multivariate logistic regression analysis were conducted to determine the associations between social determinants and sexual behaviors. Results The prevalence of premarital sex among the youth was 10.4%, with 15% of male youths reporting recent sexual activity and 2.8% having sexual intercourse with multiple partners. Variables significantly associated with premarital sex included older age groups (AOR = 2.81; 95% CI: 1.98–3.99), male (AOR = 7.87; 95% CI: 5.00–12.39), sales occupations (AOR = 2; 95% CI:1.12–3.57), smoking (AOR = 2.71; 95% CI:1.74–4.23), smokeless tobacco products (AOR = 1.94; 95% CI:1.12–3.34), and alcohol consumption (AOR = 2.97; 95% CI:2–4.41). Variables significantly associated with recent sexual activity included older age groups (AOR = 2.1; 95% CI:1.46, 3.03), being unmarried (AOR = 9.34; 95% CI:5.19–16.82), smoking (AOR = 2.01; 95% CI:1.33–3.05), use of smokeless products (AOR = 1.7; 95% CI:1.98–3.67), and alcohol consumption (AOR = 1.91; 95% CI:1.30–2.82). Youths using smokeless products had higher odds (AOR = 3.33; 95% CI:1.75–6.35) of having multiple sexual partners compared to those youths not using smokeless products. Conclusion Social determinants, along with smoking and alcohol consumption, were associated with sexual behaviors among youth. This study highlights the need for multicomponent health promotion (new public health) interventions which consider multi-level strategies, including culturally tailored sexual health programs, drug use behaviors, healthy lifestyle choices, comprehensive sexual health education for evidence-based interventions.